Risk, Choice and Social Disadvantage: Young People's Decision-Making in a Marketised Higher Education System. (August 2015) - Clark, Sheryl; Mountford-Zimdars, Anna; Francis, Becky
Rising tuition fees in England have been accompanied by a policy mandate for universities to widen participation by attracting students from socio-economically disadvantaged backgrounds. This article focuses on one such group of high achieving students and their responses to rising tuition fees within the context of their participation in an outreach scheme at a research-intensive university in the UK. Our findings suggest that rather than being deterred from attending university as a result of fee increases, these young people demonstrated a detailed and fairly sophisticated understanding of higher education provision as a stratified and marketised system and justified fees within a discourse of 'private good.' Our analysis situates their 'risk' responses within the discursive tensions of the fees/widening participation mandate. We suggest that this tension highlights an intensified commodification of the relationship between higher education institutions and potential students from disadvantaged backgrounds in which widening participation agendas have shifted towards recruitment exercises. We argue that an ongoing effect of this shift has resulted in increased instrumentalism and a narrowing of choices for young people faced with the task of seeking out 'value for money' in their degrees whilst concurrently engaging in a number of personalised strategies aimed at compensating for social disadvantage in a system beset by structural inequalities.